Validation of the Indonesian version of the non-motor symptoms scale for Parkinson’s disease - Natadidjaja, Stella; Sekeon, Sekplin; Tumewah, Rizal (International Journal of Research in Medical Sciences, 2023)
Background: Non-motor symptoms are common, have a wide range of symptoms, and have emerged as a key determinant of poor quality of life (QoL) in Parkinson’s disease (PD) patients, contributing to severe disability, and shortened life expectancy. However, although common, the non-motor symptoms of PD are often not well recognized and under-reported in clinical practice. This study aimed to translate the origin non-motor symptoms scale for PD (NMSS), which was written in English, into an Indonesian version and to evaluate its reliability and validity. Methods: Linguistic validation and psychometric analysis of the Indonesian version of NMSS were conducted in 70 patients with PD using a cross-sectional study. The acceptability, reliability, and construct validity of NMSS were analyzed. Test-retest reliability was assessed over a time interval of 14 days in all patients. Results: The 70 patients were assessed (median age 67.5 years; 57.1% males; median duration of illness 48 months; median Hoehn and Yahr stage: 3). Mean NMSS was 51.86 (SD 44.02; median 37). Neither floor nor ceiling effect was observed on the Indonesian version of the NMSS total score. Validity test using Pearson product moment showed all 9 domains Indonesian version of NMSS were valid (r=0.506-0.805, p<0.001). NMSS total score showed satisfactory reliability (Cronbach’s α coefficient on the total score was 0.852, the range for domains: 0.146-0.814). Conclusions: Indonesian version of NMSS showed good reliability and validity for the assessment of non-motor symptoms in PD patients in Indonesia.